PERBEDAAN FREKUENSI GELOMBANG ULTRASONIK TERHADAP PENURUNAN KEPADATAN LALAT DI KANTIN PT. X - Syiar Ramadhan, Ganendra Yuval; Wahyudin, Dindin; Nurhayati, Ati (Jurnal Sanitasi Profesional Indonesia, 2023)
A high degree of health will affect the body's excellent performance. PT. X provides facilities for employees to consume food in the canteen. Canteens that do not have good sanitation can have an impact on health. Insects that often appear and fly around the canteen area are flies. Flies are vectors or nuisance animals with phyla arthropoda and orderdiptera. Purpose of knowingthe difference in the frequency of ultrasonic waves to the decrease in the density of flies. This type of quasi-experimental research with pre-test post-test without control design. Populationall the flies in the canteen, the sample is part of the flies that land on flygrill in the canteen with a sample size of 6 repetitions with 3 treatments, so that the sample size was 18 before the treatment and 18 after the treatment. The data collection tool is a fly grill, thermohygrometer, and hand counter. Data collection techniques by measuring the density of flies, temperature and humidity. Sampling technique incidental sampling. Data analysis using One-way Anova. Results: the average decrease in fly density after being treated with 45 kHz, 55 kHz, and 65 kHz was 23%, 36% and 61%. Referring to PERMENKES No. 70 of 2016 for quality standards for the density of flies is ≤ 2 tail. There is a large difference in the frequency of ultrasonic waves to the decrease in the density of flies. Suggestion: further research is needed regarding the length of time for measuring fly density adjusted to fly activity of at least 3 hours and increasing the size of the ultrasonic frequency wave. For the industry, by adding the length of treatment time so that the results of reducing the density of flies are in accordance with regulatory references.